ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KESADARAN KEWAJIBAN PERPAJAKAN PADA SEKTOR USAHA KECIL DAN MENENGAH (UKM) - Putri, Eskasari; Purbasari, Heppy; Handayani, Meiga Trisna; Ulynnuha, Ovi Itsnaini (Universitas Muhammadiyah Surakarta, 2018)
This study aims to examine the influence of taxpayer knowledge, understanding of self assessment system, taxpayer income level and easiness in performing tax payment system to awareness of taxation obligation on small and medium business sector. The sample in this research are 44 respondents who are owners of small and medium enterprises located in Central Java region. The results in this study were collected through questionnaires that were processed and analyzed by using multiple regression analysis. The method used in determining the sample in this study is Convenience Sampling. The data quality test used in this research is Pearson Correlation validity test and reliability test using Cronbach Alpha. To test the hypothesis in this study, this study uses adjusted R2 test, F test, and t test. The results of this research data indicate that the knowledge of taxpayers, understanding the self assessment system, and the income level of the taxpayer does not affect the awareness of tax obligations. While the easiness variable in performing tax payment system affect the awareness of tax obligation.Â Keywords: Knowledge of taxpayer, understanding of self assessment system, income taxpayer level, easiness in performing tax payment system, awareness of taxation obligation.